Role of Non-Coding RNAs in Post-Transcriptional Regulation of Lung Diseases - Soni, Dharmendra Kumar; Biswas, Roopa (Frontiers in Genetics, 2021)
Non-coding RNAs (ncRNAs), notably microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), have recently gained increasing consideration because of their versatile role as key regulators of gene expression. They adopt diverse mechanisms to regulate transcription and translation, and thereby, the function of the protein, which is associated with several major biological processes. For example, proliferation, differentiation, apoptosis, and metabolic pathways demand fine-tuning for the precise development of a specific tissue or organ. The deregulation of ncRNA expression is concomitant with multiple diseases, including lung diseases. This review highlights recent advances in the post-transcriptional regulation of miRNAs and lncRNAs in lung diseases such as asthma, chronic obstructive pulmonary disease, cystic fibrosis, and idiopathic pulmonary fibrosis. Further, we also discuss the emerging role of ncRNAs as biomarkers as well as therapeutic targets for lung diseases. However, more investigations are required to explore miRNAs and lncRNAs interaction, and their function in the regulation of mRNA expression. Understanding these mechanisms might lead to early diagnosis and the development of novel therapeutics for lung diseases.